Question #253d6
1 Answer
Here's what I got.
Explanation:
You know that two quadratic equations
3x^2 + px + 1 = 0" " " "color(purple)((1))
and
2x^2 + qx + 1 = 0" " " "color(purple)((2))
have a common root and that the following relationship exists between
2p^2 + 3q^2 -5pq + 1 = 0
Now let's assume that
3 * color(blue)(n)^2 + p * color(blue)(n) + 1 = 0
and
2 * color(blue)(n)^2 + q * color(blue)(n) + 1 = 0
This is equivalent to saying that
3n^2 + pn + color(red)(cancel(color(black)(1))) = 2n^2 + qn + color(red)(cancel(color(black)(1)))
Rearrange to get the value of
3n^2 - 2n^2 + pn - qn = 0
n^2 + n(p-q) = 0
n * (n + p-q) = 0 implies {(n=0), (n + p - q = 0 <=> n = q - p) :}
SInce
Check to see if the given relationship is true, first for equation
3 * (q-p)^2 + p * (q-p) + 1 = 0
3q^2 - 6pq + 3p^2 + pq - p^2 + 1 = 0
This is equal to
2p^2 + 3q^2 - 5pq + 1 = 0color(white)(x)color(green)(sqrt())
and the nfor equation
2(q-p)^2 + q(q-p) + 1 = 0
2q^2 - 4pq + 2p^2 + q^2 - qp + 1 = 0
This will once again give
2p^2 + 3q^2 - 5pq + 1 = 0color(white)(x)color(green)(sqrt())